First confirmed records of the Pantanal Cat, Leopardus colocola braccatus (Cope, 1889), in the state of São Paulo, Brazil - Breviglieri, Crasso Paulo B.; Castro, Mariela C.; Ribeiro, Douglas C. [UNESP]; de Oliveira e Souza, Lúcio; Dias, João Henrique Pinheiro; Montefeltro, Felipe Chinaglia [UNESP] (Pensoft Publishers, 2018)
The Pantanal Cat, Leopardus colocola braccatus, presents a broad distribution over several biomes in South America. However, the distribution of the species is based on a limited number of occurrences, and confirmed records of the species are scarce. Here, we present 2 confirmed records of Leopardus colocola braccatus from the state of São Paulo, southeast Brazil. Both records are juvenile individuals, 1 recorded in the municipality of Castilho and the other in Araçatuba. These São Paulo records expand the distribution of this uncommon felid to the most populous state of Brazil. This species is currently Data Deficient on the São Paulo Red List, and these new records may help with future assessments of the conservation status of this felid.
Keywords: Cerrado; Colocola group; Felidae; Pampas cat; Urban area